Hyperspectral microscopy as an analytical tool for nanomaterials. (22nd January 2015) - Roth, Gary A.; Tahiliani, Sahil; Neu‐Baker, Nicole M.; Brenner, Sara A.
<x xml:space="preserve">Abstract</x> Hyperspectral microscopy is an advanced visualization technique that combines hyperspectral imaging with state‐of‐the‐art optics and computer software to enable the rapid identification of materials at the micro‐ and nanoscales. Achieving this level of resolution has traditionally required time‐consuming and costly electron microscopy techniques. While hyperspectral microscopy has already been applied to the analysis of bulk materials and biologicals, it shows extraordinary promise as an analytical tool to locate individual nanoparticles and aggregates in complex samples through rapid optical and spectroscopic identification. This technique can be used to not only screen for the presence of nanomaterials, but also to locate, identify, and characterize them. It could also be used to identify a subset of samples that would then move on for further analysis via other advanced metrology. This review will describe the science and origins of hyperspectral microscopy, examine current and emerging applications in life science, and examine potential applications of this technology that could improve research efficiency or lead to novel discoveries. WIREs Nanomed Nanobiotechnol 2015, 7:565–579. doi: 10.1002/wnan.1330 For further resources related to this article, please visit the WIREs website.